Effects of wearing a cloth face mask on performance, physiological and perceptual responses during a graded treadmill running exercise test. Issue 2 (13th April 2021) - Driver, Simon; Reynolds, Megan; Brown, Katelyn; Vingren, Jakob L; Hill, David W; Bennett, Monica; Gilliland, Taylor; McShan, Evan; Callender, Librada; Reynolds, Erin; Borunda, Nate; Mosolf, John; et al.
Abstract : Objectives: To (1) determine if wearing a cloth face mask significantly affected exercise performance and associated physiological responses, and (2) describe perceptual measures of effort and participants' experiences while wearing a face mask during a maximal treadmill test. Methods: Randomised controlled trial of healthy adults aged 18–29 years. Participants completed two (with and without a cloth face mask) maximal cardiopulmonary exercise tests (CPETs) on a treadmill following the Bruce protocol. Blood pressure, heart rate, oxygen saturation, exertion and shortness of breath were measured. Descriptive data and physical activity history were collected pretrial; perceptions of wearing face masks and experiential data were gathered immediately following the masked trial. Results: The final sample included 31 adults (age=23.2±3.1 years; 14 women/17 men). Data indicated that wearing a cloth face mask led to a significant reduction in exercise time (−01:39±01:19 min/sec, p<0.001), maximal oxygen consumption (VO2 max) (−818±552 mL/min, p<0.001), minute ventilation (−45.2±20.3 L/min), maximal heart rate (−8.4±17.0 beats per minute, p<0.01) and increased dyspnoea (1.7±2.9, p<0.001). Our data also suggest that differences in SpO2 and rating of perceived exertion existed between the different stages of the CPET as participant's exercise intensity increased. No significant differences were found between conditions after the 7-minute recovery period. Conclusion: Cloth face masks led to a 14% reduction in exercise time and 29% decrease in VO2 max, attributed to perceived discomfort associated with mask-wearing. Compared with no mask, participants reported feeling increasingly short of breath and claustrophobic at higher exercise intensities while wearing a cloth face mask. Coaches, trainers and athletes should consider modifying the frequency, intensity, time and type of exercise when wearing a cloth face mask.